If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5x + 5 = 1 Reorder the terms: 5 + 3x + -5x = 1 Combine like terms: 3x + -5x = -2x 5 + -2x = 1 Solving 5 + -2x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 1 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 1 + -5 -2x = 1 + -5 Combine like terms: 1 + -5 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| 9b=60 | | (7+22)*8=8x | | Csquared-10c=0 | | 7+22=8x | | b=60 | | 6a+9b=4500 | | a+21=-56 | | 4[5+2(3)-3]= | | 2c=c+17 | | v=4/3pi5^3 | | 6x^5+7x= | | 12x+7=10x | | 585.00+0.13b=850.00 | | 3c=c+34 | | 585+0.13b=850 | | 1x-5+14=8 | | 1.5x-5+14=8 | | 8Z+5=6Y+3 | | p=3q^3 | | 8m+3n-4m+8n= | | 930/30000= | | 6+55x=33+10 | | 0.9999999999999999999999999999999999999999999+x=1 | | a=-3n-8 | | (3+5x)(3+6x)= | | -9n+5=50 | | 208=2x+8(-4-4x) | | 2x+5=3y+3 | | 6.08+x=10 | | 6.0+x=10 | | 4y-10c=20 | | 2=.71*3 |